Blood collection, components preparation and distribution in Iran, 2008–2012. Issue 1 (February 2016) - Omidkhoda, Azadeh; Amini Kafi-Abad, Sedigheh; Pourfatollah, Ali Akbar; Maghsudlu, Mahtab
Abstract: Background: The information about the dynamics of blood collection, components preparation and distribution in Iran was measured and compared during 2008–2012. Study designs and methods: The survey instruments were based on collecting data from all 220 blood collections and blood processing centers over the country, registering them in the validated data base and reporting them to headquarter of Iranian Blood Transfusion Organization. Results: Total blood collection increased during this period, and in 2012 represented a 12.6 percent increase compared to that in 2008. On average, red blood cells, fresh frozen plasma and platelet concentrate were prepared from 95.5 ± 2.4, 81 ± 3.8 and 47 ± 8.8 percent of all whole blood collection. From 2008 to 2011, the distribution of whole blood and fresh frozen plasma revealed different patterns. For whole blood, declines were noted, while for fresh frozen plasma increases were reported. In addition the distribution of red blood cells and platelet concentrate did not change considerably. Also between 2008 and 2012, the mean percentage of outdated and discarded units was 3.6 ± 1 and 5.2 ± 4.6. Conclusion: This study as a first national survey provides comprehensive information about the blood supply, components preparation and distribution, and helps to define strategy for the future.